Pengaruh Edukasi Farmasis atau Apoteker terhadap Manajemen Diri Pasien Diabetes Melitus Tipe 2 - Miya Hartini Nur Wakhid; Windi Tri Wahyuni; Maulidiyah Cholifah; Silvi Novita Permatasari; Silvia Nur Diana Putri; Magdalena Kasmin Belaon Lebuan; Alfu Laila; Bella Fevi Aristia; Eka Putri Nurhidayah (Jurnal Medika Nusantara, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease with increasing prevalence and can lead to serious complications if not properly managed. This condition is caused by insulin resistance or insufficient insulin secretion, which can result in severe complications if neglected. This study uses a literature review method to analyze the role of education and pharmaceutical care in improving medication adherence, blood glucose control, and patient quality of life. The results show that interventions such as counseling, home pharmacy care, and booklet-based education significantly enhance patient adherence and therapy effectiveness. In conclusion, the active role of pharmacists in education and pharmaceutical care is crucial to supporting optimal T2DM management.